2016
DOI: 10.1007/s00464-016-5108-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of standard-pressure and low-pressure pneumoperitoneum on shoulder pain following laparoscopic cholecystectomy: a randomised controlled trial

Abstract: CTRI/2016/02/006590.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
0
23
0
8
Order By: Relevance
“…Low-pressure (8-9 mmHg) pneumoperitoneum was established. It is reported that low-pressure pneumoperitoneum is advantageous in reducing the incidence of shoulder and neck pain 13,14 ; the ERAS society points to its potential in mitigating the negative impact of CO 2 15,16 . 2.…”
Section: Surgerymentioning
confidence: 99%
“…Low-pressure (8-9 mmHg) pneumoperitoneum was established. It is reported that low-pressure pneumoperitoneum is advantageous in reducing the incidence of shoulder and neck pain 13,14 ; the ERAS society points to its potential in mitigating the negative impact of CO 2 15,16 . 2.…”
Section: Surgerymentioning
confidence: 99%
“…Various studies on shoulder tip pain post cholecystectomy under low pressure had shown similar results. [7][8][9][10] There were no long term complications.…”
Section: Discussionmentioning
confidence: 87%
“…4,5 Their safety, efficacy, near-equal operative time and surgeon's satisfaction appear to be comparable with standard-pressure pneumoperitoneum. [18][19][20] Patients drain group had a statistically significant longer stay as compared to the group without drain due to the fact that none of patients in the drain group could be discharged before removal of the drain. Authors conclude that the routine use of a drain in elective uncomplicated laparoscopic cholecystectomy in patients with liver cirrhosis has nothing to offer; in contrast, it is associated with increased pain.…”
Section: Discussionmentioning
confidence: 97%